5
$\begingroup$

I'm trying to prove this question:

Let $f:\mathbb R\to \mathbb R$ a function such that $f(x+y)=f(x)\cdot f(y)$, $f(0)=1$ and $f'(0)=a$. Show that $f(x)=e^{ax}$, for every $x\in \mathbb R$.

First of all I'm trying to prove that this function is positive, but even that it's difficult to me, I know that this function is never zero, because if there is $y \in \mathbb R$ such that $f(y)=0$, then $f(x-y+y)=f(x-y)\cdot f(y)=0$, then $f(x)=0$ for every $x\in \mathbb R$.

I need help to prove the positivity and hints to follow from that point.

Thanks a lot in advance.

$\endgroup$
3
  • 2
    $\begingroup$ Show that $f$ is differentiable (in particular, continuous). $\endgroup$ Feb 8 '13 at 7:43
  • $\begingroup$ @QiaochuYuan what's the gain showing that? thank you for your comment. $\endgroup$
    – user42912
    Feb 8 '13 at 7:49
  • $\begingroup$ If you can show that $f$ is continuous, $f(0) = 1$ together with the fact that $f$ is never zero implies that $f$ is positive. $\endgroup$ Feb 9 '13 at 3:03
5
$\begingroup$

for positivity:

$f(x) = f(\frac{x}{2} +\frac{x}{2})=f^2(\frac{x}{2})\geq 0$

hint for the problem:

take $g(x) =\ln f(x)$ then $g(x+y) =g(x) +g(y)$ so $g(x) =ax$

$\endgroup$
6
  • $\begingroup$ Thank you very much for your answer!!! you helped me a lot. $\endgroup$
    – user42912
    Feb 8 '13 at 7:57
  • 1
    $\begingroup$ I think the last step needs a bit of justification. Let $\mathbb{R}$ be thought of as a vector space over $\mathbb{Q}$. Let $\{b_{-1}, b_0 = 1, b_1, ...\}$ be a basis and let $\phi(b_{-1}) = 1$ and $\phi(b_i) = 0$ for $i \geq 0$ and extend $\phi$ to be linear. This is not of the form $\phi(x) = kx$ but it does satisfy $\phi(x + y) = \phi(x) + \phi(y)$. At some point we need to use the differentiability condition. $\endgroup$
    – muzzlator
    Feb 8 '13 at 8:23
  • $\begingroup$ How can you argue that $g(x+y)=g(x)+g(y)$ must have $g(x)=ax$? $\endgroup$
    – user39843
    Feb 8 '13 at 8:28
  • $\begingroup$ user39843, we simply say $g'(0) = \frac{f'(0)}{f(0)} = a$ and so $\frac{g(x+h) - g(x)}{h} \rightarrow a$. This means that $g'(x) = a$ and so $g(x) = ax$. $\endgroup$
    – muzzlator
    Feb 8 '13 at 8:35
  • $\begingroup$ @user39843 we can prove that if $g(x+y)= g(x)+g(y)$, then $g(x)=\lambda x$ to see this, first of all prove to the natural numbers, after to the rational, irracional and to real numbers, did you follow me? $\endgroup$
    – user42912
    Feb 8 '13 at 15:09
6
$\begingroup$

Pardon me if my solution seems like a cop out

They've already said the derivative at $0$ is defined, so $\frac{f(h) - 1}{h} \rightarrow a$.

Now $\frac{f(x+h)-f(x)}{h} = f(x) \frac{f(h) - 1}{h}$ which as $h \rightarrow 0$ is $a f(x)$. So $f'(x) = a f(x)$ and $f(0) = 1$.

This has solution $f(x) = e^{a x}$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.